ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGNGKAPAN CORPORATE SOCIAL RESPONBILITY (CSR) (studi kasus pada perusahaan sektor kosmetik dan keperluan rumah tangga yang terdaftar di BEI ) Tahun 2012-2016 - Utami, Dwi; Panjaitan, Fery; Prima Nugroho, Stefanus (Jurnal Akuntansi Bisnis Dan Keuangan, 2018)
The purpose of this study was to determine the effect of foreign share ownership, public share ownership, firm size, profitability, and leverage on the disclosure of corporate social responsibility both partially and simultaneously, in the cosmetics sector companies and household interests in the 2012-2016 period. This study uses quantitative data analysis, multiple linear regression, and determination using secondary data. In the partial results using the t-test, foreign share ownership has a positive effect on CSR disclosure, public shares have no positive effect on CSR disclosure, company size does not have a positive effect on CSR disclosure, profitability does not have a positive effect on CSR disclosure and leverage does not have a positive effect on CSR disclosure. And the simultaneous results using this research f test foreign ownership, public shares, company size, profitability, and leverage also do not have a positive influence on CSR disclosure. This is based on the calculation of Fcount 2.572 smaller than Ftable 2.64 with a significant level of 0.055 b.